Hubungan Mild Cognitive Impairment (MCI) dengan Hipertensi Menggunakan Mini Mental State Examination (MMSE) - Enny Lestari; Meiliza Rausan Fikrani; Esy Maryanti (Jurnal Ilmu Kedokteran, 2015)
Mild Cognitive Impairment is a decreasing in memory, decision, language and attention with normal functionalactivity which not classified in dementia. One of risk factor of MCI is high blood pressure or hypertension. Hypertensionis >140 mmHg systolic blood pressure and >90 mmHg diastolyc blood pressure. The purpose of this research is toinforming the relation between mild cognitive impairment and hypertension in Local Women Organization (PKK RWIX Kelurahan Tangkerang Timur Pekanbaru). The research used cross-sectional analitic study method, finished onJanuari 2015. Fifty subjects of Local Women Organization (PKK RW IX) were involved in this research, they weredivided into two criterias, 31 with MCI and 19 with non MCI. Based on the research, 21 of 31 MCI were detectedwith hypertension. The Chi Square test showed there is significant relation between MCI and hypertension (p value= 0,004 ).